THE CORRELATION BETWEEN READING STRATEGIES AND READING COMPREHENSION ACHIEVEMENT OF THE SIXTH SEMESTER IN ENGLISH EDUCATION STUDY PROGRAM OF BENGKULU UNIVERSITY - Nur Olivia Siregar; Rudi Afriazi; Arasuli Arasuli (JALL (Journal of Applied Linguistics and Literacy), 2019)
This research is aimed at identifying student’s reading strategies used and students’s reading comprehension achievement. The research would like to find out whether or not there is any significant correlation between reading strategies and reading comprehension achievement at the sixth-semester students of English Education Study Program at Universitas BengkuluAcademic Year 2018/2019. The research was designed as a quantitative correlation method, the subject were 78 students and the instrument used for collecting the data were reading strategies questionnaire and reading test. The collected data were analyzed by SPSS 23. The result of this research revealed that there is a significant correlation between reading strategies and reading comprehension achievement because the correlation coefficient is 0.033 which is very weak correlation category. It seems that most of the students were not familiar to the strategies in reading comprehension therefore more understanding of strategies is needed until a reading comprehension problem is solved.Keywords: Correlation, Reading Strategies, Reading comprehension Achievement